Impact of a double catastrophe, war and COVID-19, on health service utilization of a tertiary care hospital in Tigray: an interrupted time-series study - Hiluf Ebuy Abraha; Mengistu Hagazi Tequare; Hale Teka; Micheal Berhe Gebremedhin; Kibrom Gebreselassie Desta; Mohamedawel Mohamedniguss Ebrahim; Awol Yemane; Sintayehu Misgina Gebremariam; Kibrom Berhanu Gebresilassie; Tesfay Hailu Tekle; Mussie Tesfay Atsbaha; Ephrem Berhe; et al. (Conflict and Health, 2023)
Abstract Background In developing nations with fragile healthcare systems, the effect of war is likely to be much worse than it would be in more developed countries. The presence of COVID-19 will also likely exacerbate the war’s impact. This study set out to determine the effect of armed conflict and the COVID-19 pandemic on health service utilization at Ayder Comprehensive Specialized Hospital, in the Tigray region of Ethiopia. Methods An interrupted time-series study design was used to analyze patient visits over forty-eight consecutive months (from July 2017 to June 2021) at inpatient, outpatient, and emergency departments. Data were analyzed using segmented regression analysis with a defined outcome of level and trend changes in the number of patient visits. In addition, negative binomial regression analysis was also used to estimate the impact of both COVID-19 and the war on patient flow. Results There were 59,935 admissions, 876,533 outpatient visits, and 127,872 emergency room visits. The effect of COVID-19 was seen as soon as the Tigray regional government imposed comprehensive restrictions. Immediately after COVID-19 appeared, all the service areas exhibited a significant monthly drop in visits; [-35.6% (95% CI: -48.2%, -23.1%)] for inpatient, [-60.6% (95% CI: -71.6%, -49.5%)] for outpatient, and [-44.1% (95% CI: -59.5%, -28.7%)] for emergency department visits. The impact of the war became apparent after a lag time of one month. Controlling the effects of time and COVID-19, the war led to a significant fall in inpatient visits [-44.3% (95% CI: -67.2%, -21.5%)], outpatients [-52.1% (95% CI: -82.7%, -21.5%)], and emergency-room attendances [-45.0% (95% CI: -74.8%, -15.2%)]. An upward trend in outpatient flow was observed after the war [1,219.4 (95% CI: 326.1, 2,112.8)]. Conclusions The present study has clearly indicated that the war and COVID-19 have led to a large reduction in admissions, outpatient attendance, and emergency department visits. The evidence from this study suggests that due to this double catastrophe, thousands of patients could not gain access to healthcare, with probable negative consequences. Governments and organizations should implement measures to buttress the healthcare system to maintain pre-war status of service.